PENGARUH EFEKTIVITAS PENGENDALIAN INTERNAL, KETAATAN ATURAN AKUNTANSI, BUDAYA ORGANISASI TERHADAP KECURANGAN AKUNTANSI PADA LEMBAGA PERKREDITAN DESA (LPD) SE-KECAMATAN DENPASAR SELATAN - Ni Putu Ayu Candra Wahyuni; Putu Nuniek Hutnaleontina (Hita Akuntansi dan Keuangan, 2022)
Researchers in South Denpasar Sub-District hope to learn more about the role that factors like internal control effectiveness, adherence to financial reporting standards, and company culture play when it comes to detecting and preventing fraud in village credit institutions (LPDs). At the South Denpasar Village Credit Institute, this study was carried out. A total of 226 employees from the LPD Sub-District of South Denpasar are included in this study. Purposive sampling was used to collect the samples, and a total of 86 people agreed to participate in the survey. SPSS 23 is used to present the results of statistical analyses such as descriptive statistics, classical assumption tests, and multiple linear regression. According to the findings of this study, internal control effectiveness, adherence to accounting rules, and organizational culture all contribute to the prevalence of accounting fraud. The findings of this study can be used in the design of accounting fraud-prevention regulations and policies.